The Relationship of Quality of Pharmacy Services to Satisfaction Regular Outpatient Patients in the Hospital Pharmacy Installation Dr. Moewardi Surakarta with SWOT Analysis - Juniartini; Oetari; Wijayanti, Tri (Jurnal Multidisiplin Madani, 2024)
Pharmaceutical services cannot be separated from patient satisfaction where patient satisfaction is the "result" of the provision of health services, this can be understood as one of the objectives to improve the standard of pharmaceutical services and patient satisfaction with pharmaceutical services. the purpose of this study was to find out the correlation of pharmaceutical services with the level of satisfaction of regular outpatients at the Pharmaceutical Installation of  Dr. Moewardi Surakarta Hospital with Swot analysis.. Data analysis was carried out by calculating pharmaceutical service indicators adjusted to the standard, then questionnaire data was tested for validity and reliability and analyzed bivariate then the results were analyzed by SWOT analysis to determine the grand strategy matrix, dispensing time, non-recombinant drugs 49.92 minutes, concocted drugs 19.04 minutes, completeness of PIO 72.5%, no incidence of medication error 100%. Respondents' perceptions of pharmaceutical service satisfaction are satisfied, and there is a relationship between the five dimensions of pharmaceutical services and outpatient satisfaction at the pharmaceutical installation of Dr. Moewardi Surakarta Hospital, the grand matrix of swot analysis strategies is in quadrant 1 so that Dr. Moewradi Hospital uses the S-O (Strenght- Opportunity) strategy